Efeito de inibidores de bomba de prótons sobre a sensibilidade e melanogênese de Sporothrix spp - Nobre, Augusto Feynman Dias (2023)
Sporotrichosis is a subcutaneous infection caused by dimorphic fungi belonging to the clinical clade of Sporothrix spp. Fungi have several virulence factors, such as biofilm formation and melanin production, which contribute to their survival in the host and in the environment. The use of proton pump inhibitors has already been shown to inhibit the growth and melanogenesis of other fungi. Therefore, the aim of this study was to evaluate the effect of the proton pump inhibitors (PPIs) omeprazole (OMP), rabeprazole (RBP), lansoprazole (LSP), esomeprazole (ESP) and pantoprazole (PTP) on the sensitivity and melanogenesis of Sporothrix spp., as well as their interactions with clinically used antifungals. Twelve strains of Sporothrix spp. (6 Sporothrix. brasiliensis, 3 Sporothrix globosa and 3 Sporothrix schenckii). The antifungal activity of PPIs was evaluated by the broth microdilution method. The effect of the combination of PPIs with the antifungals amphotericin B, itraconazole and terbinafine was performed using the checkerboard method. The action of PPIs on the Sporothrix spp. was analyzed by crystal violet staining and MTT reduction assay methods. The action of PPIs in the melanogenesis process was carried out using the gray scale, verifying the percentage of black. OMP and RBP showed the best minimum inhibitory concentration (MIC) results, ranging from 32 to 256 µg/ml for OMP and 32 to 128 µg/ml for RBP. Biofilms were sensitive to OMP and RBP, with a reduction (p<0,05) in metabolic activity of 52% for OMP and 50% for RBP at a concentration of 512 μg/ml, and of biomass by 53% for OMP and 51% for RBP at concentrations of 512 µg/ml. As for the inhibition of melanogenesis, only OMP showed inhibition, with a 54% reduction in the gray scale. It concludes that the proton pump inhibitors OMP and RBP have antifungal activity against planktonic cells and biofilms of Sporothrix spp., in addition to OMP presenting inhibitory activity of the melanogenesis of these fungi.